2001
DOI: 10.1055/s-2001-16230
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Heparin Plasma Lipoprotein Lipase Mass: Correlation With Intra-Abdominal Visceral Fat Accumulation

Abstract: Pre-heparin plasma LPL mass is closely associated with intra-abdominal fat distribution, and the measurement of its value gives useful information concerning metabolic disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 7 publications
5
45
0
Order By: Relevance
“…We and other groups have reported that intra-abdominal visceral fat area assessed by CT at umbilical level had an inverse relationship to LPL mass and activity in PHP [26][27][28]. Similar results were obtained on the association between intra-abdominal visceral fat and pre-heparin LPL mass [19] by recruiting a total of 58 subjects comprising 50 hyperlipidemic and 8 normolipidemic subjects.…”
Section: Relationship Between Plasma Lpl Mass and Intra-abdominal Vissupporting
confidence: 83%
See 3 more Smart Citations
“…We and other groups have reported that intra-abdominal visceral fat area assessed by CT at umbilical level had an inverse relationship to LPL mass and activity in PHP [26][27][28]. Similar results were obtained on the association between intra-abdominal visceral fat and pre-heparin LPL mass [19] by recruiting a total of 58 subjects comprising 50 hyperlipidemic and 8 normolipidemic subjects.…”
Section: Relationship Between Plasma Lpl Mass and Intra-abdominal Vissupporting
confidence: 83%
“…We have shown that plasma LPL mass correlated positively with serum HDL-C level and inversely with serum TG level, but did not significantly correlate with low-density lipoprotein (LDL)-C [19]. Other group in Japan has reported similar results for 377 Japanese individuals who underwent annual health examinations [14].…”
Section: Relationship Of Serum Lpl Concentration With Lipoproteins Anmentioning
confidence: 68%
See 2 more Smart Citations
“…Kobayashi et al 11,55) also reported a link between the increase of visceral fat volume and low preheparin LpL mass concentration. These findings suggest that therapy to reduce visceral fat volume can be expected to lead to an increase of preheparin LpL mass concentration.…”
Section: Effects Of Telmisartan Therapy On Preheparin Lpl Mass Concenmentioning
confidence: 99%